Association Between Maternal Iodine Intake in Pregnancy and Childhood Neurodevelopment at Age 18 Months. Issue 2 (19th November 2018) - Zhou, Shao J; Condo, Dominique; Ryan, Philip; Skeaff, Sheila A; Howell, Stuart; Anderson, Peter J; McPhee, Andrew J; Makrides, Maria
Abstract: There are limited and inconsistent data suggesting that mild iodine deficiency in pregnancy might be associated with poorer developmental outcomes in children. Between 2011 and 2015, we conducted a prospective cohort study in Australia examining the relationship between maternal iodine intake in pregnancy and childhood neurodevelopment, assessed using Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III), in 699 children at 18 months. Maternal iodine intake and urinary iodine concentration (UIC) were assessed at study entry (<20 weeks' gestation) and at 28 weeks' gestation. Maternal iodine intake in the lowest (<220 μg/day) or highest (≥391 μg/day) quartile was associated with lower cognitive, language, and motor scores (mean differences ranged from 2.4 (95% confidence interval (CI): 0.01, 4.8) to 7.0 (95% CI: 2.8, 11.1) points lower) and higher odds (odds ratios ranged from 2.7 (95% CI: 1.3, 5.6) to 2.8 (95% CI: 1.3, 5.7)) of cognitive developmental delay (Bayley-III score <1 standard deviation) compared with mothers with an iodine intake in the middle quartiles. There was no association between UIC in pregnancy and Bayley-III outcomes regardless of whether UIC and the outcomes were analyzed as continuous or categorical variables. Both low and high iodine intakes in pregnancy were associated with poorer childhood neurodevelopment in this iodine-sufficient population.